Pengaruh Kegiatan Paper Clay Terhadap Aspek Perkembangan Seni Rupa Pada Anak Usia 4-5 Tahun - Lailatul Maghfiroh; Naning Yuliani (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
this study aims to determine the effect of paper clay activities on aspects of fine art development in children aged 4-5 years at TK DWP Menganti II Gresik. This research is a quantitative experimental method with a pre-experimental design using a one group pretest-posttest design approach. The population is 27 children in TK DWP Menganti II Gresik by using non probability sampling technique with saturated sampling. The independent variable in this study is paper clay activities, while the dependent variable is the development aspect of fine arts. In this study, the average value 27,81 was obtained from the ability of children before getting to know paper clay activities. Then the average value of 39,33 was obtained from the child’s ability after getting to know paper clay activities. Supported by the acquisition of nonparametric statistical calculations marked with the Wilcoxon signed rank test, the Asymp.Sig (2-tailed) value of 0,00 < 0,05 means Ho is rejected and Ha is accepted. From these results, it can be stated that paper clay activities affect aspect of fine art development in children aged 4-5 years at TK DWP Menganti II Gresik.